Characterization of two novel HLA‐DQB1*06:02:01 variants, identified in Brazilian individuals. (29th January 2020) - Vianna, Romulo; Turner, Thomas; Georgiou, Xenia; Porto, Luís Cristóvão
Abstract : Characterization of two novel HLA‐DQB1*06:02:01 variants, HLA‐DQB1*06:02:01:05 and ‐DQB1*06:02:01:06 .